Training on the implementation and evaluation of the merdeka curriculum for kindergarten teachers in Tangerang City - Fitria Budi Utami; Yogi Gumilar; Maya Lestari (Universitas Muhammadiyah Magelang, 2024)
One of the obstacles faced by teachers is the lack of adequate training and support from the government regarding the implementation of the Merdeka Curriculum. Even though teachers have a crucial role in the success of curriculum development, including in the implications and evaluation steps. This empowerment aims to make a positive contribution to improving the quality of education at the kindergarten level, by the objectives of the Merdeka Curriculum which prioritizes freedom and responsiveness in the learning process. This community service method takes the form of merdeka curriculum implementation training and is packaged in the form of a workshop on December 28, 2023. Participants in this activity are kindergarten teachers in Tangerang consisting of 20 participants from Al Wildan Islamic School. The results of this community service received a positive response and a high level of satisfaction from the participants. This shows that the workshop was successful in providing insight, practical experience, and significant scientific improvement.